Determinasi Kinerja Perumda AM di Bangka Belitung: Peran Roe, Solvabilitas, Ebitda, dan Motivasi Karyawan (2018–2023) - Nur Nabila; Az-Zahra Nayla Rosa; Aziza Aziza; Alya Aprilia; Erwinsyah Erwinsyah (As-Syirkah: Islamic Economic & Financial Journal, 2025)
This study analyzes the influence of Return on Equity (ROE), solvency, EBITDA, and employee motivation on the performance of the Regional Public Drinking Water Company (Perumda AM) in the Bangka Belitung Islands Province for the 2018-2023 period using a quantitative approach with secondary data from annual reports and multiple linear regression analysis. The results indicate that ROE significantly influences company performance (sig. 0.041 < 0.05), while solvency (sig. 0.619), EBITDA (sig. 0.719), and employee motivation (sig. 0.170) do not. The Adjusted R Square coefficient of determination is 0.208, explaining 20.8% of the variation in performance. This finding confirms the inconsistency of previous research and emphasizes the role of profitability in the context of regional public service companies.